On the Odd Prime Solutions of the Diophantine Equation xy+yx=zz - Yuanyuan Deng; Wenpeng Zhang (Abstract and Applied Analysis)
Using the elementary method and some properties of the least solution of Pell’s equation, we prove that the equation xy+yx=zz has no positive integer solutions (x,y,z) with x and y being odd primes.